Imaging Features of Triple Negative Breast Cancers : Mammography, Ultrasound and Magnetic Resonance Imaging = Značajke snimki trostruko negativnih karcinoma dojke : mamografija, ultrazvuk i magnetska rezonancija - Ivanac, Gordana; Džoić Dominković, Martina; Bojanić, Kristina; Kelava, Tomislav; Dumić-Čule, Ivo; Canecki-Varžić, Slvija; Smolić, Martina; Včev, Aleksandar; Smolić, Robert; Brkljačić, Boris (2021)
Breast cancer (BC) is a highly heterogeneous disease. Aim was to evaluate imaging features of triple negative breast cancers (TNBC) in comparison to non-TNBC. We reviewed data of 30 patients who had been diagnosed as having TNBC and 37 patients with non-TNBC (control group) using criteria described for mammography (MMG), ultrasound (US) and magnetic resonance imaging (MRI) in Breast Imaging-Reporting and Data System (BI-RADS) lexicon for image interpretation. Age of patients, size of tumor, multifocality, histological type, tumor grade and status of lymph nodes were reviewed. TNBC were more often histological grade 3 and had significantly more positive lymph nodes at the time of diagnosis on pathology reports. On MMG, US and MRI TNBC mostly appeared as regularly shaped masses. On US as hypoechogenic masses with no posterior acoustic features and on MRI as masses with rim type of enhancement, fast wash-in and plateau type of curves. Most frequent category reported after MMG and US was BI RADS 4, and after MRI BI RADS 5. In conclusion, our study confirmed higher histological grade of TNBC, as well as more frequent lymph node involvement in comparation to the non-TNBC. TNBC showed tendency to affect younger women and to be larger than non-TNBC. Although, they most often presented as a mass on mammography and sonography, in a significant number of cases they remained miscategorized, due to the benign imaging features. All cases are recognized on MRI where they appear as rim enhancing masses.
Rak dojke (RD) vrlo je heterogena bolest. Cilj istraživanja bio je procijeniti slikovne značajke trostrukog negativnog karcinoma dojke (TNRD) u usporedbi s ne-TNRD-om. Pregledali smo podatke 30 pacijenata kojima je dijagnosticiran TNRD te 37 pacijenata s ne-TNRD-om (kontrolna skupina) koristeći kriterije opisane za mamografiju (MMG), ultrazvuk (US) i magnetsku rezonancu (MRI) u Breast Imaging-Reporting and Data System (BI-RADS) za interpretaciju slike. Analizirana je dob pacijenata, veličina tumora, multifokalnost, histološki tip, gradus tumora i status limfnih čvorova. TNRD-i su češće bili histološki gradus 3 i znatno su više imali pozitivne limfne čvorove u vrijeme dijagnoze na patohistološkim izvješćima. Na MMG-u, US-u i MRI-u TNRD-i su se uglavnom pojavljivali kao pravilno oblikovane mase, na US-u kao hipoehogene mase bez stražnjih akustičnih značajki, a na MRI-u kao mase koje rubno nakupljaju kontrasno sredstvo, uz dinamičke krivulje s brzim nakupljanjem i platoom. Najčešća kategorija zabilježena nakon MMG-a i US-a bila je BI RADS 4, a nakon MRI-a BI RADS 5. U zaključku je naša studija potvrdila viši histološki gradus TNRD-a, kao i češće zahvaćanje limfnih čvorova u odnosu na kontrolnu skupinu. Pokazali smo tendenciju pojavljivanja kod mlađih žena, kao I veće dimezije u odnosu na kontrolnu skupinu. Iako su se najčešće predstavljali kao tvorba na MMG-a i USu, u određenome broju slučajeva pogrešno su kategorizirani zbog benignih slikovnih značajki. Svi su slučajevi na MRI-u dijagnosticirani kao masa koja rubno nakuplja kontrastno sredstvo.
Bibliografija
Summary.